AAFD: Is the Gastroc Just Pulling Some Strings?. Issue 3 (September 2019) - Chang, Song Ho; Waryasz, Gregory R.; Morris, Brandon; Hagemeijer, Noortje; Guss, Daniel; DiGiovanni, Christopher W.
Abstract : Whether ankle equinus predominantly contributes to or ensues from an adult-acquired flatfoot deformity (AAFD) remains unknown. Regardless of the exact nature of this relationship, current evidence supports a distinct role for concomitant gastrocnemius recession or Achilles tendon lengthening during surgical correction of significant AAFD deformity. Achieving the appropriate degree of surgical correction for components of ankle equinus, hindfoot valgus, and/or Chopart collapse that may contribute to AAFD requires proper clinical evaluation and an appreciation of contributory pathophysiology. Review of recent literature describing gastrocnemius contracture and its potential role in AAFD provides a platform from which to approach this challenging problem. Level of Evidence: Diagnostic Level V. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is available in the text.